1999
DOI: 10.1149/1.1392608
|View full text |Cite
|
Sign up to set email alerts
|

Visible Electroluminescence from n‐Type Porous Silicon/Electrolyte Solution Interfaces: Time‐Dependent Electroluminescence Spectra

Abstract: Visible electroluminescence (EL) from n-type porous silicon (n-PS) in an electrolyte solution containing S 2 O 8 2Ϫ was investigated by potential-sweep and potential-step methods. Potential sweep measurements showed that both the cathodic current and EL intensity increased and the EL spectra blue-shifted as the potential became negative. These characteristics were further studied by the potential-step method. Immediately after the potential was stepped to a negative value, the cathodic current began to flow an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 54 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the PSi can emit PL in spite of being an indirect semiconductor because there is nanocrystalline Si in the porous layer [15], and the band gap depends on the particle size of the nanocrystalline Si in accord with the quantum size effect [16][17][18]. Crystalline Si does not show PL because of the quantum band structure having an indirect band gap of about 1.1 eV and a small exciton binding energy (below 15 meV) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the PSi can emit PL in spite of being an indirect semiconductor because there is nanocrystalline Si in the porous layer [15], and the band gap depends on the particle size of the nanocrystalline Si in accord with the quantum size effect [16][17][18]. Crystalline Si does not show PL because of the quantum band structure having an indirect band gap of about 1.1 eV and a small exciton binding energy (below 15 meV) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Further work on luminescence in porous silicon was published in the Journal in 1999. This included a paper by Noguchi et al, 197 which described the visible EL from n-type porous silicon in an electrolyte solution. Time-resolved EL spectra measurements showed that the EL spectrum was blue-shifted with time.…”
Section: Survey Of Luminescence Papers Published In the Journal In Th...mentioning
confidence: 99%